Rural change in South Asia : India, Pakistan, Bangladesh - Etienne, Gilbert (New Delhi : Vikas Pub. House, 1995)
Focussed on the rural economy and its link with the economic reforms.
Includes bibliographical references (p. [336]-343) and index.
Keywords: Rural development -- India; India -- Social conditions -- 1947-; India -- Economic conditions -- 1947-; Rural development -- Pakistan; Pakistan -- Economic conditions; Rural development -- Bangladesh; Bangladesh -- Social conditions; Bangladesh -- Economic conditions